Ke kvalifikátoru kolokviální v »Akademickém slovníku současné češtiny« - Štěpán, Josef (Bohemistyka, 2020)
The article deals with the concepts of colloquial-standard Czech, everyday Czech and common Czech. The concept of the standard Czech and its norm is analysed in more detail; this analysis is used also as a starting point for the evaluation of words from the point of view of their (non-)standardness. The paper criticises the broad definition and use of the qualifier kolokviální, used for the units of the spoken informal language in the article by P. Kochová and Z. Opavská devoted to the preparation of the Academic Dictionary of the Contemporary Czech. Instead of the qualifier colloquial delimited in this way, the author proposes – on the data of univerbation units, loanwords and new meanings – to use both the qualifier non-standard and the newly more narrowly delimited qualifier colloquial, which would correspond to the qualifier colloquial-standard in the existing dictionaries. The article arrives to the conclusion that the conception of P. Kochová and Z. Opavská would disrupt the integrity of the standard Czech, because with their broadly delimited qualifier colloquial non-standard words would enter into the standard Czech.